Utility of Opportunistic Infections, Joints’ Involvement and Accuracy of Various Screening Tests to Diagnose Rheumatoid Arthritis Patients - Ahmad, Ausaf; Khan, Ashfaque; Khan, Abdur Raheem; Ahmed, Hashim; Alajam, Ramzi Abdu; Alshehri, Mohammed M.; Ganesan, Bhuvanesh Babu Mondey; Dayah, Salma Jabril Abu; Shaphe, Mohammad Abu; Alameer, Abdulaziz H.; Esht, Vandana (Medicina (Kaunas, Lithuania), 2023)
Background and Objectives: Rheumatoid Arthritis (RA) is an auto-immune disease in which the body mistakenly considers some parts of its own system as pathogens and attacks them. Prevalence is approximately 0.75% in India. About 40% of the diseased become work disabled within 5 years from the onset of symptoms. The objective of this paper is to assess the sign/symptoms, joints’ involvement, difficulties in daily activities and screening accuracy of serology tests of clinically suspected RA patients. Material and Methods: A cross-sectional cohort study design was conducted on two hundred ninety clinically suspected subjects who were referred by different OPDs of hospitals for screening. The profiles of study subjects were carried through a semi-structured, pre-tested schedule method. About 2 mL of blood samples were collected in a plain vial from each patient and tested for diagnostic tests RF, CRP and AntiCCP by using RF-Latex, CRP Latex and ELISA method, respectively, by the laboratory persons. Results: Joint pain shows to be a leading problem in RA as compared to other signs and symptoms. The majority of the study subjects suffer from knee problems (62%). Approximately equal numbers of RA-positive cases were screened by RF and AntiCCP tests. The CRP test screened about one-third of cases. CRP+ AntiCCP, RF+ AntiCCP and RF + CRP all have good sensitivity, and RF+ AntiCCP + CRP has a very high sensitivity for diagnosing RA. Conclusions: This study found that a substantiation of a major proportion of clinically suspected RA patients were suffering from knee pain. Predication of AntiCCP increased the possibility for the diagnosis of RA. However, RF was also moderately related to the diagnosis of RA, and the combination of both tests was more valuable.